Physico‑chemical, microbial and phytotoxicity evaluation of composts from sorghum, finger millet and soybean straws - Jagadabhi, P.S.; Wani, S.P.; Kaushal, M.; Patil, M.; Vemula, A.K.; Rathore, A. (Springer, 2019)
Purpose Composting is an environmentally sustainable alternative for bioconversion of agricultural residues into a nutrient-rich product that can enhance soil fertility/microbial diversity and thereby improve agricultural productivity. The goal of the current study was to evaluate the decomposition pattern of the agro-residues and assess the maturity and phytotoxicity of the composts obtained using physico-chemical, microbial and statistical analyses. The study also attempted to determine a threshold germination index (GI) to serve as a maturity index for the composts by conducting seed germination assays with tomato, chickpea and soybean seeds.